Electricity Consumption and Economic Growth in Turkey: A Mixed Frequency Var Approach - Berksun, Dilara; Dogan, Nukhet; Berument, M. Hakan (Energy Economics Letters, 2021)
This paper investigates the relationship between monthly electricity consumption, quarterly GDP, and quarterly components of GDP using the Mixed Frequency VAR (MF-VAR) model for Turkey for the period from 1987:2Q to 2017:3Q. When the conventional quarterly VAR model is used, any causal relationship between electricity consumption and GDP growth could not be found. However, when we used the MF-VAR specification, we found that electricity consumption does increase GDP growth; this supports to the growth hypothesis but not the conservation hypothesis. Repeating the same exercise by adding other low frequency variables, the empirical evidence still reveals that an increase in electricity consumption increases GDP. However, an increase in electricity consumption increases Private Consumption, Investment, Imports expenditures, Construction, Industrial, Manufacturing, and Service Sector outputs more than it increases GDP. In addition to this, the empirical evidence reveals that an increase in electricity consumption increases Agricultural sector output less than it increases GDP.